Primary Causes of Death in Patients with Non-Hodgkin’s Lymphoma: A Retrospective Cohort Study - Mei, Mei (Cancer Manag Res, 2020)
PURPOSE: Non-Hodgkin’s lymphoma (NHL) comprises many serious hematologic malignancies from lymphocytes. The incidence of NHL is 5.1 per 100,000, with a mortality rate of 2.5 per 100,000 worldwide. However, the causes of death among patients with NHL vary. This retrospective cohort study aimed to elucidate the primary causes and specific risk factors for NHL. PATIENTS AND METHODS: The study included patients who were diagnosed from January 2006 to January 2018. Grouped by sex, Ann Arbor stage, date of diagnosis, age, B symptom, NHL type, international prognostic index, and Eastern Cooperative Oncology Group (ECOG) performance score, the Log-rank test was performed, and survival curves were drawn using the Kaplan–Meier method. The competing-risks regression model was used to analyze the specific causes of death. RESULTS: T-cell lymphoma, B symptoms and worse performance were associated with a lower survival. Mortality from NHL accounted for most and other common causes that contributed to death included circulatory and respiratory diseases. Patients diagnosed with T-cell lymphoma were more likely to die of NHL rather than other causes. Moreover, patients with B symptoms on admission were more likely to die of diseases of the circulatory system. Lastly, patients diagnosed at an earlier age suffered more from diseases of the digestive system and immune mechanism or other uncommon causes. CONCLUSION: Classifications of subtypes, age and occurrence of B symptoms were factors providing references for a specific cause of death owing to NHL, which might enable physicians to decrease cause-specific mortality rates.